2023
DOI: 10.1111/dmcn.15563
|View full text |Cite
|
Sign up to set email alerts
|

Developmental coordination disorder subtypes in children: An unsupervised clustering

Abstract: AimTo identify subtypes of developmental coordination disorder (DCD) in children.MethodChildren with DCD diagnosed through comprehensive evaluation at Robert‐Debré Children's University Hospital (Paris, France) were consecutively enrolled from February 2017 to March 2020. We performed an unsupervised hierarchical clustering based on principal component analysis using a large set of variables encompassing cognitive, motor, and visuospatial scores (Wechsler Intelligence Scale for Children, Fifth Edition; Develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(77 reference statements)
1
2
0
Order By: Relevance
“…In line with previous data on visuospatial abilities in the DVSD profile, we expect this group to obtain the lowest scores, as compared to the ND group, in all the measures assessing visuospatial processing, including VSPT (Fisher et al, 2022;Mammarella et al, 2023). On the other hand, we expect to find more heterogeneous performances for the DCD group in tasks assessing visuospatial processing (Gras et al, 2023). As regards the comparison between the two clinical groups (i.e., DVSD and DCD), although considering the lack of studies that have directly compared these populations, based on recent findings (Cardillo et al, 2024), we expect to find a more severe impairment in the visuo-spatial domain for the DVSD group as compared to the DCD peers.…”
Section: The Present Studysupporting
confidence: 87%
See 2 more Smart Citations
“…In line with previous data on visuospatial abilities in the DVSD profile, we expect this group to obtain the lowest scores, as compared to the ND group, in all the measures assessing visuospatial processing, including VSPT (Fisher et al, 2022;Mammarella et al, 2023). On the other hand, we expect to find more heterogeneous performances for the DCD group in tasks assessing visuospatial processing (Gras et al, 2023). As regards the comparison between the two clinical groups (i.e., DVSD and DCD), although considering the lack of studies that have directly compared these populations, based on recent findings (Cardillo et al, 2024), we expect to find a more severe impairment in the visuo-spatial domain for the DVSD group as compared to the DCD peers.…”
Section: The Present Studysupporting
confidence: 87%
“…Along with DVSD, Developmental Coordination Disorder (DCD) may present with difficulties in visuospatial processing, although huge heterogeneity is reported (Cardillo et al, 2024). More in depth, some studies concluded for the presence of visuospatial impairments in this population (e.g., Van Waelvelde et al, 2004;Tsai et al, 2008;Gras et al, 2023), while others did not find any impairment (i.e., Bonifacci, 2004). Such heterogeneity in performances, albeit being reconducible to intra-group variability, well documented in neurodevelopmental disorders (e.g., Van Waelvelde et al, 2004;Tsai et al, 2008), may be attributed to methodological differences in the studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation